A novel cold-chain free VCG-based subunit vaccine protects against Chlamydia abortus-induced neonatal mortality in a pregnant mouse model - Richardson, Shakyra; Bell, Courtnee R.; Medhavi, Fnu; Tanner, Tayhlor; Lundy, Stephanie; Omosun, Yusuf; Igietseme, Joseph U.; Eko, Francis O. (Frontiers in Immunology, 2023)
Chlamydia abortus (Cab) causes spontaneous abortion and neonatal mortality in infected ruminants and pregnant women. Most Cab infections are asymptomatic though they can be treated with antibiotics, signifying control of these infections may require alternative strategies, including the use of effective vaccines. However, the limitations imposed by live attenuated and inactivated vaccines further suggest employment of subunit vaccines may need to be considered. The efficacy of a newly generated Vibrio cholerae ghost (rVCG)-based subunit vaccine harboring the N-terminal portion of the Cab Pmp18D protein (rVCG-Pmp18.3) in preventing Cab-induced abortion or neonatal mortality was evaluated in pregnant mice. Mice were intranasally (IN) immunized and boosted twice, two weeks apart with the vaccine, and immunized and unimmunized mice were caged with males four weeks postimmunization. The mice were then infected either IN or transcervically (TC) 10 days after pregnancy, and the fertility rate was determined seven days postpartum. Eight days after delivery, the mice were sacrificed and Cab infectivity in the lungs and spleens was evaluated by culturing tissue homogenates in tissue culture. Our results demonstrated that the vaccine induced immune effectors that mediated complete clearance of infection in the lungs and significantly reduced Cab infectivity in the spleen following IN immunization. Vaccine immunization also afforded protection against Cab-induced upper genital tract pathology (uterine dilation). Furthermore, while there was no incidence of abortion in both immunized and unimmunized mice, immunized mice were completely protected against neonatal mortality compared to unimmunized infected controls, which lost a significant percentage of their litter seven days postpartum. Our results establish the capability of the rVCG-Pmp18.3 vaccine to prevent infection in the lungs (mucosal) and spleen (systemic) and protect mice from Cab-induced tubal pathologies and neonatal mortality, a hallmark of Cab infection in ruminants. To advance the commercial potential of this vaccine, future studies will optimize the antigen dose and the number of vaccine doses required for protection of ruminants.